Integrated Urban and Per-Urban Agriculture into Urban Planning as a Strategy to Enhance Food Security in Bondo Town - Masawa, Sarah Oloo (JOOUST, 2014)
Due to rapid growth in populations in urban areas, the food requirements of urban centres have enormously increased in recent years. Agriculture and food planners have to think how best to meet these food requirements without _putting stress on resources and polluting the environment. One of the possibilities is to grow food.r'especially perishable high-value vegetables, in and around urban centres. Therefore, the potential for Urban and Peri-Urban agriculture (UPUagr) cannot be underscored, most especially its contribution towards improving the poor livelihood status and enhancement of urban environmental management by closing the loop on urban waste resources. The major challenge in Kenya is that UPUagr lacks supportive local policy and legal framework recognizing the socio-economic value of UPUagr. Its integration in broad urban development plans with minimal conflict is also a problem. The study was conducted in 2011, at Bondo Sub County, Bondo Town Council through field studies at Nyawita, Barkowino and Ajigo sub locations. The overall objective of this study was to assess the extent to which Urban and Peri-urban Agriculture is integrated into Bondo Urban Planning achievement of sustainable food security to enhance food security. The objectives were to examine planning strategies suitable for integrating UPUagr into urban planning and to identify major constraints to UPUagr in Bondo town. The study employed descriptive survey design. Proportionate method was used to determine the sample size of 368 households and 248 traders. Key informants from relevant Government Ministries and Non-Governmental Organizations were incorporated. Respondents were identified through purposive and random sampling (Primary data was collected using questionnaires, interview schedules, participants' observation, photographs. Qualitative data was analyzed through sub-themes and themes as they emerged. Quantitative data was analyzed using l descriptive statistics. The results showed that Urban and Peri-urban Agriculture complemented rural agriculture. UPUagr had made important contributions to social, economic and ecological objectives of Sustainable Urban Development. The wide-ranging positive contribution of Urban and Peri- Urban Agriculture show its importance to a city's well-being, and the need to incorporate it in a city's comprehensive plan. The major constraint in the Sub County was drought. The study recommended intensification of extension service provision and creation of special programs in UPUagr by both Government and Non-Governmental Organizations. The local government in planning the upcoming towns, to develop a framework to act as the basis for developing policies that are more pragmatic for UPUagr and the adoption of modern techniques of fanning like aquaponics, hydroponics and greenhouses.